ANALISIS PENGARUH KINERJA PERBANKAN TERHADAP DANA PIHAK KETIGA BANK PERSERO - iqbal firdausi (Jurnal Keuangan dan Perbankan, 2016)
This study aimed to analyze the effect of the performance of banks consisting of CAR, ROA, ROA, LDR simultaneously and partially on the Third Party Funds and analyze between the performance of banks consisting of CAR, ROA, ROA, LDR the dominant influence on the Third party Fund. Forms of this research is descriptive explanatory nature of causality through hypothesis testing. The number of samples in the study of 4 Bank Limited for 11 years i.e. from 2004 to 2014 year. The analysis technique used multiple regression analysis. The analysis showed that the performance of banks consisting of CAR, ROA, ROA, LDR simultaneously affect the Third Party Funds. Performance of banks consisting of CAR, ROA, ROA, LDR partially affect the Third Party Funds. ROA dominant influence on Third Party Funds.